Microstructure and wear behaviour of powder and suspension hybrid Al2O3–YSZ coatings - Murray, James W.; Leva, Alessandro; Joshi, Shrikant; Hussain, Tanvir (Elsevier, 2018)
Suspension based plasma sprayed coatings can yield superior microstructural and tribological properties compared to conventional powder based plasma sprayed coatings. This study investigates a new hybrid method, using simultaneous spraying from powder and suspension, to produce composite coatings using alumina and yttria stabilised zirconia (YSZ), with potentially excellent wear and thermal properties. Dry sliding wear showed the alumina suspension-YSZ suspension coating yielded half the specific wear rate of the alumina powder-YSZ suspension, explained by preferential gamma alumina formation and increased porosity in the latter. Both YSZ-containing samples showed superior toughness and wear rate than simple alumina powder and suspension coatings.